The accurate determination of Perfluorooctane sulfonic acid (PFOS) removal efficiency by integrated-sonochemical system - Debabrata Panda; Maxime Cochennec; Stéfan Colombano; Benjamin Laulier; Pascal Tierce; Alexandre Baudouard; Sebastian Bristeau; Anne Togola; Julie Lions; Nicolas Devau; Eric D. van Hullebusch (Ultrasonics Sonochemistry)
Perfluorooctanesulfonic acid (PFOS) is one of the most investigated Per- and polyfluoroalkyl substances (PFAS) for being the strongest compound to eliminate and having adverse health concerns. In this work, we have conducted the sonochemical treatment of PFOS simulated water under high (500 kHz) and low (22 kHz) frequencies while monitoring the operational parameters via an integrated sonochemical system. The integrated advanced sonochemical system includes software to monitor treatment power, solution temperature and frequency while allowing distinctive control of the reaction conditions. Considering the lack of calorimetric measurements in earlier studies and the difficulty in achieving comparative outcomes, precise calorimetric measurements and determination of electrical energy per order (EEO) were performed in this study. The complete PFOS removal was achieved under 500 kHz frequency with optimum parameters including initial pollutant concentration (5 mg/L), ultrasound power density (400 W/L) and solution temperature (25 °C) within 180 min of treatment. The removal and mineralization extents (defluorination) were determined by ultra-high performance liquid chromatography–mass spectrometry (UPLC-MS/MS) and ion-chromatography (IC) analysis. Under optimum conditions, 100 % removal and 99 % mineralization were achieved. The rate constant (k) ranged from 0.011 to 0.031 min-1 (first-order reaction), which increased with the increase in the power density. While the solution temperature did not significantly affect the PFOS removal efficiency, the initial concentration was found to have a prominent effect on the reaction rate constant. However, experiments at low frequency (22 kHz) showed negligible removal efficiency. The specific energy requirement for reaching 90 % removal while considering the power consumed by the ultrasonic system from the main electrical source was determined to be 700 kWh/m3, which is much lower than other reported work under similar conditions. This work will be useful for both laboratory and industrial upscaling while acting as a benchmark reference to follow.